ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI TINGKAT PRODUKSI SELADA AIR (STUDI DESA WRINGIN ANOM KECAMATAN PONCOKUSUMO KABUPATEN MALANG) - Rifatin Amalia; Idah Zuhroh; Syamsul Hadi (Jurnal Ilmu Ekonomi JIE, 2020)
This study aims to analyze the effect of land area, labor, production facilities costs on the results of watercress production in Poncokumo District, Malang Regency in one season. The data used is primary data, which obtained through direct field interviews with 35 watercress farmers. The method in this study is quantitative. The result shows that the land area and the cost of production facilitie have a positive and significant effect on the production of watercress. While labor has a significant negative effect on the production of watercress.